Plan-Do-Check-Act dalam Upaya Perbaikan Mutu Tata Tertib Santri di Pondok Pesantren Mahasiswa An-Nahdlah Kebumen - Fatimah Toifatul Inganah; Agus Salim Chamidi (LPPM IAINU Kebumen, 2023)
The purpose of this study was to find out how the implementation of PDCA (Plan-Do-Check-Act) is in an effort to improve the quality of student discipline at the An-Nahdlah Student Islamic Boarding School, Kebumen. The informants in this study were caregivers, administrators, and students of the An-Nahdlah Kebumen Islamic Boarding School. The method used in this study is using a qualitative approach. Data collection techniques used in this study include three methods, namely: observation, interviews, documentation. The data analysis technique used is the Miles and Huberman model which consists of data reduction, data display, and drawing conclusions. The results of the study show that efforts to improve the quality of the discipline of students at the An-Nahdlah Kebumen Student Islamic Boarding School use PDCA. In the planning process, improving the quality of the rules regarding obligations and prohibitions. In the implementation process, socializing and monitoring the implementation of obligations and prohibitions. In the monitoring process, checking and analyzing the quality of the implementation of the code of conduct and determining the priority of corrective action. In the repair process, make improvements to the rules regarding obligations and prohibitions so that new rules are created.